EFEKTIVITAS PELAYANAN PESERTA KARTU INDONESIA SEHAT (KIS) - Putri, Tasya Amelia; Abdi, Abdi; Wardah, Wardah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The purpose of this study is to determine the effectiveness of services for Healthy Indonesia Card (KIS) participants at the Tanete Health Center, Bulukumpa District, Bulukumba Regency. The type of research used is qualitative which is descriptive. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and conclusions. The results showed that (a) the accuracy of the program target, less effective where there were still people who belonged to the prosperousl category but were KIS participants, (b) program socialization, showed that it had been effective because the program had been known by the general public, (c) program objectives, were effective where it was in accordance with the objectives of the KIS program, and (d) program monitoring, was considered effective where monitoring had been integrated.